A qualitative comparison of position-based routing protocols for ad-hoc networks - Qabajeh, L.K.; Kiah, M.L.M.; Qabajeh, M. (2009)
Wireless Ad-Hoc networks are collection of nodes that can communicate without any fixed infrastructure. A crucial problem in Ad-Hoc networks is finding an efficient route between a source and a destination. The need for scalable and energy efficient protocols, along with the recent availability of small, inexpensive and low power positioning instruments justify introducing position based routing algorithms in mobile Ad-Hoc networks. This paper presents an overview and a qualitative comparison of the existing Ad-Hoc routing protocols that make forwarding decisions based on the geographical position of a packet's destination. We conclude our findings by investigating opportunities for future research.